Compliance with best practice recommendations for colonoscopy bowel preparation among hospitalized patients at a tertiary adult hospital. Issue 4 (14th December 2022) - Ullah, Hamid; Chima, Charles C.
ABSTRACT: Introduction: Proper bowel preparation is essential to successful colonoscopies. The quality of bowel preparation is often poorer in the inpatient settings compared with outpatient settings. This can result in repeat procedures and increased hospital length of stay. Objective: The aim of this evidence implementation project was to assess and improve compliance with best practice recommendations for bowel preparation prior to colonoscopy. Methods: The project was done in three phases for patients hospitalized at a tertiary adult hospital: the initial audit; clinical practice change that included providing patients with both oral and written education about bowel preparation; and a follow-up audit. Results: The baseline audit showed that the hospital was already fully compliant with two out of four best practice criteria. For two criteria with poor compliance rates at baseline, we improved compliance for criterion 1 (giving patients both oral and written education about bowel preparation) from 8 to 40%, while compliance rate for criterion 4 [using 2 l polyethylene glycol – (PEG) or adding ascorbic acid to 4 l PEG] remained at 0% at the end of the intervention. Conclusion: The JBI evidence implementation program provided a structured approach to analyze colonoscopy bowel preparation practices and develop strategies to align policies with the best practice recommendation of providing written education about bowel preparation. However, there is need for more conclusive evidence to identify the most ideal inpatient bowel preparation formulation.